Peran Guru dalam Menyelesaikan Konflik Santri: Resolusi Konflik di Pondok Pesantren - Moh Nawawi; Suprapto; Abdul Malik (Journal of Mandalika Literature, 2024)
Resolving conflicts between students in Islamic boarding schools requires an approach based on positive values, such as peace, tolerance, and mutual understanding. This study examines the role of teachers as mediators in conflict resolution in Islamic boarding schools, using conflict management theory that emphasizes separating problems from personal relationships and finding mutually beneficial solutions. The purpose of this study is to understand how teachers in Islamic boarding schools can manage conflicts with a constructive approach and prioritize Islamic boarding school cultural values. The method used in this study is qualitative research with a library research approach. Library research is a research method carried out by studying various books, literature, notes, and reports related to the topic being studied, in this case regarding conflict management in Islamic boarding schools. The results of the study indicate that teachers have a central role in reducing tensions and building harmonious relationships between students through dialogue and mediation. The leadership of the kyai has also been shown to strengthen the conflict resolution process by providing direction and role models. This conflict resolution not only reduces tensions, but also builds solidarity, strengthens relationships between students, and creates a more inclusive social environment. Teachers as facilitators and leaders have an important role in maintaining social harmony and character development of students in Islamic boarding schools.